Seventh Five Year Plan 1985-90 A Framework Government of Uttar Pradesh - Planning Commission (Planning Commission, 1983)
It is quite appropriate in an exercise of this nature to look back and familiarize oneself with some of the most significant trends which arc easily discernible on socio-economic scene of the state and arc relevant or helpful to future planning. A brief description of these trends, without any detailed comments or analysis is given in the following few paras. The growth in U. P. during a long period of about 23 years from 1951 to 1974 was marginal, inadequate and far less than the growth of the country as a whole, leading to serious regional imbalances in the country. This is the period when there were wide fluctuations in production of foodgrains, and with the exception of 1970-71, the margin of increase in foodgrains production from year to year or over a longer period of time was insignificant.
Planning Department, Government of Uttar Pradesh